AN INTER-ORGANIZATIONAL RELATION PERSPECTIVE OF INDUSTRIAL SERVICE QUALITY ON THE WILLINGNESS TO RECOMMEND - Irawan, Josephine Octavia; Agustiono, (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2023)
W Bali – Seminyak is one of the luxurious 5-star hotel brands under Marriott International with its own style of wedding with the brand’s signature style, sophistication, and fun. Nonetheless, achieving targeted wedding sales still poses a challenge as it only achieved 80% of targeted sales. W Bali - Seminyak needs to understand factors that form wedding planners’ willingness to recommend the place as a wedding venue. Seventy wedding planners in Bali that are registered in the company’s database will be used as the sample. Exploratory factor analysis will be used to cluster items that make a wedding planner willing to recommend W Bali – Seminyak. Exploratory Factor Analysis (EFA) was used as a statistical technique to identify underlying factors or dimensions that explain the variation in a set of observed variables. From the results of the data processed by SPSS factor analysis, it was known that there are 8 factors that contribute to the wedding planners’ willingness to recommend: perceived employee quality, client experience, output service quality, physical evidence, attractiveness, aesthetic view, additional assurance determinants, and price. This research was conducted at the beginning of Covid-19 pandemic, further studies need to be done on whether the conclusion of this paper will hold post covid-19.